Desmoplastic Small Round Cell Tumor of Stomach. (6th June 2013) - Abu-Zaid, Ahmed; Azzam, Ayman; AlNajjar, Asma; Al-Hussaini, Hussa; Amin, Tarek
Abstract : Desmoplastic small round cell tumor (DSRCT) is an extremely uncommon, highly aggressive, and malignant mesenchymal neoplasm of undetermined histogenesis. Less than 200 case reports have been documented in literature so far. Herein, we report a 26-year-old otherwise healthy female patient who presented with a 1-month history of epigastric pain. On physical examination, a palpable, slightly mobile, and tender epigastric mass was detected. All laboratory tests were normal. A chest, abdominal, and pelvic contrast-enhanced computed tomography (CT) scans showed a 3.8 × 7.2 × 8.7 cm ill-defined mass, involving gastric fundus and extending into gastric cardia and lower gastroesophageal junction. It was associated with multiple enlarged gastrohepatic lymph nodes; the largest measured 1.2 cm. There was no evidence of ascites or retroperitoneal or mesenteric lymphatic metastases. Patient underwent total gastrectomy with D2 lymphadenectomy, splenectomy, and antecolic Roux-en-Y esophagojejunal anastomosis. Histopathological examination revealed coexpression of mesenchymal, epithelial, and neural markers. The characteristic chromosomal translocation (t(11; 22)(p13; q12)) was demonstrated on fluorescence in situ hybridization (FISH) technique. Diagnosis of DSRCT of stomach was confirmed. Patient received no postoperative radiotherapy or chemotherapy. A postoperative 3-month followup failed to show any recurrence. In addition, a literature review on DSRCT is included.